Pengembangan Media Papan Susun Huruf (Pasuhu) Untuk Meningkatkan Kemampuan Menyusun Huruf Menjadi 1 Kata Pada Siswa Sekolah Dasar - Feby Renita Sari Rumapea; Nazla Della Aranditha; Ririn Khairunisa; Rolanda Silaban (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by children's ability to compose words from several letters. Students' ability to arrange letters into one word has not yet developed optimally. This can be seen during learning activities in class, where the teacher asks students to read. From there, educators took the initiative to provide other learning techniques, namely by using techniques that could motivate children more and attract children's interest in reading activities. The letter stacking board technique was chosen by educators because this technique is believed to make children more enthusiastic and more interested, so it is hoped that it can improve elementary school students' ability to arrange letters into one word. The research was carried out using the development research method. The object of this research is students' ability to arrange letters into one word using data collection techniques, namely observation, questions and documentation. The research instruments used were a scoring rubric and an assessment rubric to guide observation of data analysis techniques. This research produces a product in the form of a letter stacking board whose suitability has been tested by looking at the results of observation and validation. This typesetting board product contains attractive letters and images so it is suitable for use in class II elementary schools and has received a positive response from teachers and elementary school students.